Competitive swimming biomechanics: Freestyle - McMaster, W.; Troup, J. P. (International SportMed Journal, 2001)
This review addresses important biomechanical principles associated with competitive swimming, especially obstacles to mechanical efficiency. The various drag factors encountered are defined and addressed. Freestyle swimming is used as the example to illustrate these principles. The propulsion-force development during swimming is also reviewed to demonstrate the most efficient mechanical model. The various kinetic components of freestyle swimming are then reviewed to demonstrate their mechanical contribution to swimming speed and to delineate the kinematics of freestyle.